2023
DOI: 10.1007/s11033-023-08695-9
|View full text |Cite
|
Sign up to set email alerts
|

miRNA as biomarker in lung cancer

Esperanza Salcedo Lobera,
Macarena Arroyo Varela,
Rafael Larrosa Jimenez
et al.

Abstract: Lung cancer has a high prevalence and mortality due to its late diagnosis and limited treatment, so it is essential to find biomarkers that allow a faster diagnosis and improve the survival of these patients. In this sense, biomarkers based on miRNAs have supposed a considerable advance. miRNAs, which are small RNA sequences, can regulate gene expression, so they play an essential role not only as a diagnostic biomarker but also as a therapeutic and prognostic one. Also, miRNA biomarkers can be obtained from l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Predominantly, miRNAs exhibit imprecise complementarity to target mRNAs, and the degree of complementarity between the miRNA and the mRNA determines the mechanism through which the expression of the target gene is repressed (i.e., mRNA degradation or translation inhibition). Moreover, miRNAs are characterized by their high stability, which supports their use as biomarkers in the realm of clinical diagnostics [40][41][42]. Remarkably, miRNAs are involved in a wide range of biological functions, such as cell differentiation, cell growth, apoptosis, cell proliferation [43,44], tissue regeneration [45], immune responses, inflammation [46], and human reproduction [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Predominantly, miRNAs exhibit imprecise complementarity to target mRNAs, and the degree of complementarity between the miRNA and the mRNA determines the mechanism through which the expression of the target gene is repressed (i.e., mRNA degradation or translation inhibition). Moreover, miRNAs are characterized by their high stability, which supports their use as biomarkers in the realm of clinical diagnostics [40][41][42]. Remarkably, miRNAs are involved in a wide range of biological functions, such as cell differentiation, cell growth, apoptosis, cell proliferation [43,44], tissue regeneration [45], immune responses, inflammation [46], and human reproduction [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…They can regulate the degradation of messenger RNA (mRNA) or suppress the translation through binding to the 3’untranslated region (UTR) of the target mRNA (18). Studies have demonstrated that miRNAs are essential players in a variety of physiological and pathological processes (19–21). Mammalian kidneys can express various miRNAs.…”
Section: Introductionmentioning
confidence: 99%